Co-design of health educational materials with people experiencing homelessness and support workers: a scoping review - Rodriguez, Andrea; Shambhunath, Shambhunath; Wijesiri, Thushani Indumani Devi; Biazus-Dalcin, Camila; Mc Goldrick, Niall (Frontiers in Oral Health, 2024)
Introduction: People experiencing homelessness are often marginalised and encounter structural barriers when seeking healthcare. Community-based oral health interventions highlighted the need of well-trained practitioners for the successful engagement of service users and behaviour change. However, a lack of adequate information and specific training has been previously reported. The adoption of inclusive approaches, such as co-design, to develop tailored and meaningful health promotion training and educational materials capable of addressing the specific needs of this group is required. Co-design entails active involvement of different groups in research processes that acknowledge participants’ needs and expectations. This scoping review aims to identify the available literature on the participation of people experiencing homelessness and/or their support workers in co-designing health and oral health promotion training/educational materials, approaches adopted, and barriers and enablers to develop these materials. Methods: The Joanna Briggs Institute (JBI) Scoping Review Methodology informed the development of the scoping review. The protocol was registered on the Open Science Framework. Six electronic databases (Medline (OVID), PsychInfo (OVID), Scopus, Web of Science, Applied Social Sciences Index and Abstracts (ASSIA) (ProQuest) and CINHAL) were systematically searched using MeSH terms. An extensive grey literature search, consultation with experts and hand searching of reference lists took place. Records were screened independently and in duplicate using the Rayyan Qatar Computing Research Institute (QCRI) online tool, followed by qualitative content analysis involving descriptive data coding. Results: Eight studies/materials were included. Key approaches adopted to co-design, enablers and barriers were captured. The enablers were inclusivity, a safe environment for positive participation, empowerment and flexibility, the barriers were difficulty in recruiting and sustaining participation, power differentials, and limited resources. Conclusion: The evidence in this area is limited. This scoping review provided foundations for further research to examine the impact of different components of the co-design process including the environment in which the co-design process is conducted. Further studies with experimental design and reported using appropriate study design frameworks detailing active components of the co-design process would strengthen the evidence base in this area.